Gestión administrativa y su relación con la promoción del turismo del gobierno autónomo descentralizado de Quevedo, año 2013 - Cedeño Abril, Luis Belisario (2015)
This research work is carried out with the goal of making an analysis of the administrative management carried out by the GAD of the Canton municipal Quevedo with emphasis on the promotion of tourism, the current situation was diagnosed of such activity, was also identified as the activities undertaken by the Unit responsible for the public entity for the development and promotion of tourism. This research consists of a part or documentary theory and practice, consisting of two segments, the first corresponds to the introductory part and the second to the chapters that constitute the body of the document…..